Effect of Three Sowing Dates on the Quality Characteristics of Bread Wheat (Triticum aestivum L.) Grown in Central Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
224U. of K. J. Agric. Sci. 22(2), 224-240, 2014Effect of Three Sowing Dates on the Quality Characteristics of BreadWheat (Triticum aestivum L.) Grown in Central SudanM.G. Abdalla 1 , Hayat Abdelrahman2 and S.M. Mohamed 31, 3 Agricultural Research Corporation, Dongola Research Station2 National Food Research Centre, Grain Technology DepartmentAbstract: This research was conducted to study the effect of differentsowing dates on the quality characteristics of bread wheat (Triticumaestivum L.) grains grown in central Sudan during 2005/2006 season. Thefield experiment was executed by split plot design with three replications.Three sowing dates (November 6 th , November 21st and December 6th )were used to represent the early, mid and late sowing dates. Grain qualitycharacteristics of four released cultivars; namely, Argine, Alneilain,Debeira and Condor were studied. Characters such as 1000 - kernel(grain) weight, test weight (Hectoliter weight) and flour yield declinedprogressively with delayed sowing date (6th Dec.). Maximum values wereobtained in the early sowing date (6th Nov.) and minimum values in thelate sowing date (6th Dec.).The results showed that proper sowing dateresulted in the highest protein and gluten values in wheat grain and flour.With the late sowing date, these two parameters decreased in all cultivarstested. The cultivars Debeira and Condor were the most affected, whilethe cultivar Argine showed little effect. Argine had higher protein andgluten values than the other cultivars in the three sowing dates. Thechange of proportions of different protein components in wheat graininduced by the variation of sowing dates could be the main reason for theimprovement in wheat grain quality in Sudan.
Keywords: Sowing time; bread wheat; proximate composition; quality characteristics